2020
DOI: 10.15386/mpr-1756
|View full text |Cite
|
Sign up to set email alerts
|

A review of the current understanding of nanoparticles protein corona composition

Abstract: Upon entering into the biological environments, the surface of the nanoparticles is immediately coated with proteins and form the so-called a protein corona due to which a nanoparticle changes its "synthetic" identity to a new "biological" identity. Different types of nanoparticles have different protein binding profiles, which is why they have different protein corona composition and therefore it cannot be said that there is a universal protein corona. The composition and amount of protein in the corona depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…In this study, we have demonstrated that DND is a potent pan-cytokine adsorber. It is well known that nanoparticles effectively bind proteins to form protein coronae with some specificity exist due to their unique physicochemical properties such as size, surface charge, and hydrophobicity ( Breznica et al, 2020 ). As the size of nanoparticles decreases, the protein binding affinity increases because smaller particles have a higher surface area and a higher surface reactivity compared to their larger counterparts ( Cedervall et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have demonstrated that DND is a potent pan-cytokine adsorber. It is well known that nanoparticles effectively bind proteins to form protein coronae with some specificity exist due to their unique physicochemical properties such as size, surface charge, and hydrophobicity ( Breznica et al, 2020 ). As the size of nanoparticles decreases, the protein binding affinity increases because smaller particles have a higher surface area and a higher surface reactivity compared to their larger counterparts ( Cedervall et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many different nanomaterials have been reported to strongly interact with biological fluids and form a bio-corona, (Galmarini et al, 2018;Mandal et al, 2018;Tenzer et al, 2013;Yu et al, 2020), and this property has led to important applications, for example, as an analytical tool for the detection of different diseases (Giulimondi et al, 2019), such as cancer (Di Domenico et al, 2018). However, the formation of bio-corona is not always a desirable property: for example, it was shown that NPs without PC has higher targeting efficiency (Feiner-Gracia et al, 2017;Md Rasib et al, 2019) and cellular uptake (Breznica et al, 2020;Ghazaryan et al, 2019;Giulimondi et al, 2019.;Tonigold et al, 2018). The study of biomolecular corona, in the context of drug delivery, has been used by researchers mainly to tailor the properties of NPs for three main objectives, schematically shown in Figure 1: (i) to introduce "stealth" characteristics, (ii) to have efficient targeting, and (iii) to obtain low fouling materials.…”
mentioning
confidence: 99%
“…An emerging strategy for targeting NPs to tumors is modifying the nanoparticle surface to promote interactions with biological components that naturally target specific cells. In the presence of fluids like blood or cell culture media, NPs adsorb biomolecules forming what has been termed a “corona” . This corona is composed of proteins and possibly other biological molecules like lipids.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of fluids like blood or cell culture media, NPs adsorb biomolecules forming what has been termed a "corona". 9 This corona is composed of proteins and possibly other biological molecules like lipids. A protein corona is likely formed by two distinct layers: a hard corona made from proteins with a strong affinity for the nanoparticle surface and a soft corona consisting of proteins that may transiently interact with NPs.…”
Section: ■ Introductionmentioning
confidence: 99%